دراسة حالة التحليل بالمركبات الرئيسية لمؤشرات التنمية الحضرية ببلدية سيدي عمران ولاية المغير - ردينه, بوليف; انفال, راشدي (جامعة الوادي - University of Eloued, 2023)
"ملخص التنمية الحضرية هي تنمية واسعة تتناول كافة القطاعات والجوانب اجتماعية، اقتصادية والصحية وبدلك تضمن البحث ثلاث فصول اهتم الفصل الاول بدراسة التنمية الحضرية مفهومها، عواملها، اهدافها وكدا اطراف المشاركة فيه. اما الفصل الثاني فهتم بدراسة المؤشرات التنميةالحضرية حيث شمل مفهمومها، خصائصها وكدا انواعها واهميتها بينما اهتم الفصل الثالث والدي تضمن في سياقه الجانب التطبيقي بعنوان التحليل بالمركبات الرئيسية مفهومهاو التحليل العاملي الحضري للمؤشرات الحضرية وتحليل المؤشرات الحضرية وتحليل المؤشرات الحضرية لمدينة سيدي عمران من خلال نمودج التحليل العاملي للمؤشرات ودرجات العوامل. " Abstract Urban development is a broad development that deals with all sectors and social, economic and health aspects. Instead, the research included three chapters. The second chapter is concerned with the study of development indicatorsUrban, where it included its concept, characteristics, types, and importance, while the third chapter was concerned with, and included in its context, the applied side entitled Analysis of the main components, its concept, urban factor analysis of urban indicators, urban indicators analysis, and urban indicators analysis of the city of Sidi Omran through the factor analysis model of indicators and factor degrees.
Keywords: التنمية الحضرية، المؤشرات الحضرية، التحليل العاملي، التحليل بالمركبات الرئيسية; urban development urban indicators Factor analysis Major component analysis